Key Trends in Implementation of the Fund's Transparency Policy : 2007. (Policy Papers; Policy Paper ;, 2007)
The set of tables provided in this report updates the last Key Trends with information on documents published through December 2006. Rolling updates will continue to be issued annually to the Board.